(3aGcgI GdNdaGA heaGcgI GdXQaGAs - (3CMeO Hf eMeO Hf YHO Gddg GdMfaj, CHh eMeO TgGH GdOjf , GHf YQHTGg,J (B852 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi TgOJ GdcGFfGJ HhLhOg CeG HYO aEf Gdgd GdebOS ai PGJg bO ChOY ai cd PQI ef eNdhbGJg , ef HOjY UfYg hdWja BjGJg abUO WGFaI ef GdCPcjGA hSejJg aGcgI GdNdaGA heaGcgI GdXQaGA s
(3BNQgG (B:s
(3TYQ hgPH HGdaVd eG QJHg hQJH ai GdaUd eG gPHg hfSCd Gdgd EJeGe fYeg , hESHGd Pjd EMSGfg hcQeg GdMeO ddg QH GdYGdejf Efg cQje SJGQ Mdje ZaGQ s
(3jdi GdeNWhW JbjjOGJ cKjQIs
(3cJHJ HYV cdeGJg hCHjGJg HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B228s
Keywords: (3GdCOHs